PENGARUH LEVERAGE, CAPITAL INTENSITY, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP AGRESIVITAS PAJAK (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Siahaan Rikki Vanco Boy; Fitrios Ruhul; Odiatma Fajar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the effect of leverage, capital intensity, firmsize and profitability on tax aggressiveness. Tax aggressiveness is the dependentvariable in this study and is measured by the effective tax rate (ETR). Theindependent variables in this study are leverage, capital intensity, company sizeand profitability. The population in this study are manufacturing companies listedon the Indonesia stock exchange in 2015-2017. Samples were collected usingpurposive sampling method and obtained 54 companies as samples. The type ofdata in this study is secondary data and the analytical method used is multipleregression analysis assisted with SPSS version 21 windows. The results of thisstudy indicate that leverage and profitability effect on tax aggressiveness.Meanwhile capital intensity and firm size have no effect on tax aggressiveness.The calculation of the coefficient of determination (R2) is 0.236 which means thatoverall the independent variables used in this study explain the tax aggressivenessof 23.6% while the remaining 76.4% is explained by other independent variablesnot used in this research.Keyword : Leverage, Capital Intensity, Firm Size, Profitability and TaxAggressiveness